Resource Extraction in a Political Economy Framework - Karolina Ryszka (Tinbergen Institute, 2013)
We analyze resource extraction in a political economy setting by introducing a political leader who optimizes both his own and the society's welfare function. We find that accounting for the private utility of a political elite, its higher discount rate and a different time horizon generally speeds up extraction. The higher than optimal resource extraction is not only relevant in welfare terms, but also regarding possible consequences with respect to climate change. The effect of higher extraction caused by a political leader directly accroaching resources does not hold in a decentralized private ownership economy where the government strives to raise revenues through taxation. We endogenize the political economy framework and show that the politician's discount factor is higher than the social discount factor due to the probability of losing power. The weight that the political leader attaches to social welfare is determined by the way the probability of staying in power depends on the welfare of the society.
Keywords: Q31; Q38; Q54; 330; exhaustible resources; oil; dictatorship; political economy; taxation; climate change